2014
DOI: 10.1051/0004-6361/201322217
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the dust temperatures of galaxies in the SFR–Mplane up toz ~ 2

Abstract: We study the evolution of the dust temperature of galaxies in the SFR−M * plane up to z ∼ 2 using far-infrared and submillimetre observations from the Herschel Space Observatory taken as part of the PACS Evolutionary Probe (PEP) and Herschel Multi-tiered Extragalactic Survey (HerMES) guaranteed time key programmes. Starting from a sample of galaxies with reliable star-formation rates (SFRs), stellar masses (M * ) and redshift estimates, we grid the SFR−M * parameter space in several redshift ranges and estimat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
360
6

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(438 citation statements)
references
References 93 publications
(133 reference statements)
72
360
6
Order By: Relevance
“…These issues have been discussed and studied in Magnelli et al (2014). They found that in the GOODS-S, GOODS-N and COSMOS fields our multi-wavelength catalogues are complete for starforming galaxies with M * > 10 10 M up to z ∼ 2.…”
Section: Final Samplementioning
confidence: 98%
See 3 more Smart Citations
“…These issues have been discussed and studied in Magnelli et al (2014). They found that in the GOODS-S, GOODS-N and COSMOS fields our multi-wavelength catalogues are complete for starforming galaxies with M * > 10 10 M up to z ∼ 2.…”
Section: Final Samplementioning
confidence: 98%
“…From the best-fitting DH SED template we also estimated T dust using the pairing between dust temperature and DH templates established in Magnelli et al (2014). The reliability of these dust temperature estimates depends on the number of FIR data points available and on whether those data points encompass the peak of the FIR emission.…”
Section: Determination Of Far-infrared Properties Through Stackingmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a substantial amount of observational evidence that suggests a redshift evolution of the total IR luminosity and dust temperature (e.g. Amblard et al 2010;Elbaz et al 2010;Hwang et al 2010;Casey et al 2012;Magnelli et al 2014).…”
Section: Number Countsmentioning
confidence: 99%